DNA logic circuits based on FokI enzyme regulation. (20th January 2020) - Zhao, Sue; Liu, Yuan; Wang, Bin; Zhou, Changjun; Zhang, Qiang
Abstract : A series of DNA logic devices was constructed based on the allosteric strategy of the enzyme-assisted cleavage regulation system, which are simple in scale, modular, and work efficiently. Abstract : In biomolecular programming, researchers have attempted to use DNA molecules as a new kind of highly reliable raw material, due to the high predictability and good programmability of DNA molecules, and construct DNA circuits that can realize logical calculation. In DNA circuits with a multi-step cascade, autonomy, and complex behavior, it is very important to be able to controllably activate and regulate toeholds. Therefore, we propose a strategy using an enzyme-assisted cleavage regulation system to solve the above problems. In this strategy, the DNA input strand regulates the recognition domain of FokI and initiates the activity of FokI due to the reconfiguration of programmable information. In addition, FokI induced conformational changes regulate the toehold-mediated strand displacement reaction, which optimizes the complex function and the signal transmission of logic circuits. In order to prove the feasibility of this strategy, we constructed a series of logic gates (YES, AND, and INHIBIT), and on this basis, we successfully implemented both a demultiplexer circuit and a multiplexer cascade circuit. The proposed enzyme-assisted cleavage regulation strategy provides a new approach for constructing more complex molecular computing systems, with applications in biosensors and medical detection systems.